Effects of hydrophobic and electrostatic interactions on the escape of nascent proteins at bacterial tibosomal exit tunnel - Thuy, Bui Phuong; Le Duy, Manh; Nguyen Thi Hai, Yen; Trinh Xuan, Hoang (Communications in Physics, 2022)
We study the escape process of nascent proteins at the ribosomal exit tunnel of bacterial Escherichia coli by using molecular dynamics simulations with coarse-grained and atomistic models. It is shown that the effects of hydrophobic and electrostatic interactions on the protein escape at the E. coli's tunnel are qualitatively similar to those obtained previously at the exit tunnel of archaeal Haloarcula marismortui, despite significant differences in the structures and interactions of the ribosome tunnels from the two organisms. Most proteins escape efficiently and their escape time distributions can be fitted to a simple diffusion model. Attractive interactions between nascent protein and the tunnel can significantly slow down the escape process, as shown for the CI2 protein. Interestingly, it is found that the median escape times of the considered proteins (excluding CI2) strongly correlate with the function \(N_h + 5.9 Q\) of the number of hydrophobic residues, \(N_h\), and the net charge, \(Q\), of a protein, with a correlation coefficient of 0.958 for the E. coli's tunnel. The latter result is in quantitative agreement with a previous result for the H. marismortui's tunnel.